Eficiência de uso do nitrogênio por gramíneas e emissões de amônia em função do manejo do dejeto líquido de bovino - Silva, Alieze Nascimento da (2017)
The effects of the injection of liquid bovine waste (DLB) on the soil combined with the use of nitrification inhibitors, such as dicyanodiamide (DCD), is still poorly documented, mainly on N losses to the atmosphere via N-NH3 emission, (EUN), plant parameters and wheat and maize productivity in subtropical southern Brazil. Thus, the objective of the present work was to evaluate how the DLB application in the soil in notillage system (SPD) affects the ammonia emission (N-NH3) of the DLB in the system, as well as this practice Combined with DCD can affect EUN, plant parameters and wheat and maize yield. Four studies were conducted in the field at two distinct sites belonging to the Federal University of Santa Maria, one in Frederico Westphalen, RS, in a dystrophic Red Latosol, and the other in Santa Maria, RS, in an Alumínico (DLBs), DLBs + DCD, injected DLB (DLBi), DLBi + DCD, control and mineral fertilization (NPK) on the surface. The studies were conducted simultaneously at both sites. The application of DLB was performed manually with irrigators, while the injection was mechanized, at depth of 8-11 cm. The DCD dose used was 7 kg ha-1, mixed to the DLB instants before application to the soil. Compared to surface application, DLB injection in the soil proved to be efficient in reducing N-NH3 emissions to the atmosphere, both in wheat and maize. The efficiency of the injection was maximized when combined with DCD, increasing N-NH4 + retention in the system, also increased apparent N recovery (103%), N agronomic efficiency applied with DLBs and crop productivity compared to N Surface application. The best performance of the crops occurred in the treatment with DLB + DCD injection (DLBi + DCD). In addition, this practice was efficient in reducing N losses by volatilization of ammonia (N-NH3), guaranteeing greater N availability at Plants. In view of these results, the injection of DLB + DCD in soil in SPD is a promising alternative to soil surface application, as well as EUN, productivity and plant parameters in wheat and corn as well as beneficial In the reduction of N-NH3 emission.